The International Dimensions of Democratization in Egypt: The Limits of Externally-Induced Change - Selim, Gamal M (Springer, 2015)
This book purports to examine the international dimensions of the democratization process in Egypt in the post Cold War era; a theme which acquired significance at the academic and policy-oriented levels in light of the growing internationalization of reform arrangements in the Arab world in post 9/11 and the greater involvement of external powers in Arab politics following the Arab Spring uprisings.